Quality Characteristics of Breads Fortified with Sesame Seed (Global Journal of Medical Research, 2017)
This study evaluated the quality of bread fortified with sesame seed. Breads with added full fat and defatted sesame seed meals were baked and analysed for nutrient compositions, physical and sensory properties and storage stability. Full fat and defatted sesame seed meal respectively had 31.28% and 46.00% carbohydrate, 23.07% and 29.9% protein, 31.05% and 11.89% fat, and 13.20% and 12.14% crude fibre. Fortification with sesame seed improved the nutrient composition, storage stability, physical and sensory properties of bread. Fortification with 20% full fat or defatted sesame seed flours respectively improved protein from 11.80% to 13.93% or 14.89%, crude fibre from 1.63% to 3.44% or 5.25%, fat from 0.15% to 6.80% or 3.85%, but decreased carbohydrate from 55.44% to 50.37% and 48.68% respectively. Sensory scores (colour, texture, flavour, and overall acceptability), loaf and specific volume and shelf life of bread increased with increasing sesame seed addition.
Keywords: bread; sesame; fortification; quality; shelf-life